Software Matematika Sagemath Sebagai Media Belajar Untuk Mengetahui Kemampuan Komputasi Siswa - Siti Hotma Sari Pulungan; Yahfizam Yahfizam (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
During the period of compulsory education in Indonesia, which is 12 years, the government requires mathematics as the main subject of external learning which will continue to have an impact on people's lives. The level of ability in a field of science must be measured to obtain valid data for the development of education in Indonesia. The use of Sagemath Mathematics Software in schools in Indonesia is not surprising at this time, technological developments have made the use of Sagemath Mathematics Software commonplace. The research method used in this research uses a literature study research method where researchers research the results of previous research. In groups There were 55.88% of experiments that experienced an increase (normalized gain) in the high category and 44.22% were in the medium category. Meanwhile, the average increase (normalized profit) in this group was 0.71, which is included in the high category. The results of this study concluded that students' abilities in mathematical computational thinking on Sagemath software are very high, this is due to several factors between the tendencies of students' desires and creativity of the teaching profession. Students' computing abilities when using Sagemath software can be done through students' mathematical algorithm features.